Alat Pendeteksi Detak Jantung Menggunakan Mikrokontroler ESP32 Dan Sensor Pulse Berbasis Website - Helisati Putra Hulu; April Imelda Putri Hulu; Fazasokhi Giawa; Sukur Hati Harefa; Raheliya Br Ginting (Institut Teknologi dan Bisnis Indonesia, 2026)
In today's digital era, the demand for advanced and user-friendly healthcare devices is increasing. This research aims to design and develop a real-time heart rate detection device using an ESP32 microcontroller and a pulse sensor connected to a web platform. This device is designed to continuously monitor the user's heart rate and provide online data access, facilitating easier health monitoring.The methodology used in this research includes the design of hardware and software. The ESP32 microcontroller was chosen for its advantages in Wi-Fi connectivity and good data processing capabilities. A pulse sensor is used to detect the heart rate, while a web platform is developed to display real-time heart rate data. The research results show that this custom-built heart rate detection device can effectively detect and display real-time heart rate data. The data sent to the web platform can be accessed via computer or smartphone, making it easier for users or medical personnel to monitor health conditions remotely. In summary, this heart rate detector based on the ESP32 microcontroller and pulse sensor successfully meets the need for real-time heart rate monitoring and can be accessed via the web. Further development can be done to improve accuracy and integration with other medical systems.